Decentralizing cancer care in sub-Saharan Africa through an integrated regional cancer centre model: The case of Kenya. - Mary F Nyangasi; Angela A McLigeyo; David Kariuki; Siwillis Mithe; Albert Orwa; Valerian Mwenda (Public Library of Science (PLoS), 2023)
For 50 years, comprehensive cancer treatment services were provided at one public hospital and a few private facilities in the capital city. In 2019, the services were decentralized to new national and regional centers to increase service accessibility using an integration model. This study aimed to analyze the status of the utilization of services at regional cancer centers. We analyzed data from the district health information system, focusing on patient demographics, visit type, cancer stage, and the type of treatment provided. For comparison, a trend analysis of new cancer cases recorded at the main national referral hospital between 2011-2021 was also conducted. We conducted a descriptive analysis of the variables of interest; the median was used to summarize continuous variables and percentages were used for categorical variables. A total of 29,321 patients visited the regional centers in 2021; the median age was 57 years (IQR 44-68) and 57.3% (16,815) were female. Visits to regional centres represented 38.8% (29,321/75,501) of all visits to public cancer centers; new visits accounted for 16.4% (4814/29321), and the rest were follow-up visits. Most patients (71%) had an advanced disease. The proportion of male patients with advanced-stage cancer was significantly higher than that of female patients (74% vs. 69%, P<0.001). Of the 15,275 patients who received treatment at regional centers, 69.1% (10,550) received chemotherapy.The increased patient visits show good service uptake at the regional centers, implying improved access. These findings can inform policies that will guide future expansion and service improvement. We recommend optimizing cancer service delivery at regional centers across the care continuum to improve patient outcomes.